Investigation of Curve Diffuser Performance by Means of Installing Passive Flow Control Device: Woven Wire Mesh Screen - CHOW, KAH TECK (Research Progress in Mechanical and Manufacturing Engineering, 2024)
INVESTIGATION OF CURVE DIFFUSER PERFORMANCE BY MEANS OF INSTALLING PASSIVE FLOW CONTROL DEVICE: WOVEN WIRE MESH SCREEN